2011
DOI: 10.3109/0167482x.2011.569801
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress following childbirth in homelike- and hospital settings

Abstract: In this Dutch study, 1 in 100 women had PTSD following childbirth, with no differences between home- and hospital deliveries after controlling for complications and interventions. Emergency cesarean section, severe labor pain, and poor coping skills were associated with more posttraumatic stress symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 34 publications
(80 reference statements)
9
94
0
2
Order By: Relevance
“…The significant positive correlations between the IES-R-J-PWV and JEPDS confirmed that the IES-R-J-PWV instrument adequately evaluated childbirth-related postnatal posttraumatic stress symptoms among Japanese women at one month after childbirth. Consistent with another study [16], our study also showed moderate negative correlations between posttraumatic stress symptoms and sense of coherence. Consequently, this offers further evidence that the IES-R-J-PWV can evaluate childbirth-related postnatal stress symptoms.…”
Section: Ies-r-j-supporting
confidence: 92%
See 2 more Smart Citations
“…The significant positive correlations between the IES-R-J-PWV and JEPDS confirmed that the IES-R-J-PWV instrument adequately evaluated childbirth-related postnatal posttraumatic stress symptoms among Japanese women at one month after childbirth. Consistent with another study [16], our study also showed moderate negative correlations between posttraumatic stress symptoms and sense of coherence. Consequently, this offers further evidence that the IES-R-J-PWV can evaluate childbirth-related postnatal stress symptoms.…”
Section: Ies-r-j-supporting
confidence: 92%
“…A higher score reflects better stress management. Previous studies reported that a low sense of coherence was associated with higher postnatal posttraumatic stress symptoms scores, and postnatal posttraumatic stress symptoms were significantly negatively correlated with sense of coherence [16,40,41]. Therefore we adopted the SOC-13 to examine criterion-related validity.…”
Section: Sense Of Coherence-13 (Soc-13) Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Women may have late presentation of symptoms due to being overwhelmed with having a new baby. The symptoms may also be ascribed to post-natal depression (PND) (Beck, 2011), as the rates of comorbidity between PTSD and PND are high (Stramrood et al, 2011). As women are repeatedly exposed to the reminder of their trauma (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The other group consists of papers assessing the SOC in relation to mental comorbidities of somatic diseases and issues. These include cancers (Ezer, Chachamovich, Saad, Aprikian, & Souhami, 2012;Langius & Lind, 1995;Siglen, Bjorvatn, Engebretsen, Berglund, & Natvig, 2007), myocardial infarction (Benyamini, Roziner, Goldbourt, Drory, & Gerber, 2013), heart transplantation (Ruzyczka et al, 2011), lumbar spinal stenosis (Sinikallio et al, 2006), Morbus Parkinson (Pusswald et al, 2009), kidney diseases (e.g., Klang, Bjorvell, & Cronqvist, 1996), rheumatoid arthritis (Buchi et al, 1998), systemic sclerosis (Hyphantis et al, 2007), traumatic child birth experiences (Stramrood et al, 2011), critical accidents (Schnyder et al, 2000), and critical diseases in general (Fok, Chair, & Lopez, 2005).…”
Section: The Soc In Relation To Physical Symptomsmentioning
confidence: 99%